DEFICIENCIA ECONÓMICA EN GESTIÓN SOCIAL DE LA SOCIEDAD DE BENEFICENCIA PÚBLICA - CALLAO - Arrunategui Aguirre, Juan Antonio (2016)
The investigation has provided knowledge of the causes of the problematic reality of the Public Benefit Society of Callao, in relation to its profitability and liquidity, preventing the entity of effectively meeting its goals and objectives. In consequence, we believe that its existence is justified to the extent that it is necessary to assist the excluded population in extreme poverty and vulnerable groups; nonetheless this does not mean a non-compliance with the normal administrative and operational functioning of the oldest institution in Callao.